ANALYSIS OF ZAKAT FUND MANAGEMENT IN EMPOWERING MSME’S OF LAZIZ MUHAMMADIYAH (LAZIZMU) AT CITY OF MEDAN - Khairunnisa Khairunnisa; Juwita Purnama Sari (Proceeding International Seminar of Islamic Studies, 2021)
Research with the title